A Case of Intragenic Recombination Dramatically Impacting the Phage WO Genetic Diversity in Gall Wasps - Zhu, Dao-Hong; Su, Cheng-Yuan; Yang, Xiao-Hui; Abe, Yoshihisa (Frontiers in Microbiology, 2021)
The phage WO was characterized in Wolbachia, a strictly intracellular bacterium causing several reproductive alterations in its arthropod hosts. This study aimed to screen the presence of Wolbachia and phage WO in 15 gall wasp species from six provinces of southern China to investigate their diversity and prevalence patterns. A high incidence of Wolbachia infection was determined in the gall wasp species, with an infection rate of 86.7% (13/15). Moreover, seven species had double or multiple infections. All Wolbachia-infected gall wasp species were found to harbor phage WO. The gall wasp species infected with a single Wolbachia strain were found to harbor a single phage WO type. On the contrary, almost all species with double or multiple Wolbachia infections harbored a high level of phage WO diversity (ranging from three to 27 types). Six horizontal transfer events of phage WO in Wolbachia were found to be associated with gall wasps, which shared identical orf7 sequences among their respective accomplices. The transfer potentially took place through gall inducers and associated inquilines infected with or without Wolbachia. Furthermore, 10 putative recombination events were identified from Andricus hakonensis and Andricus sp2, which harbored multiple phage WO types, suggesting that intragenic recombination was the important evolutionary force, which effectively promoted the high level of phage WO diversity associated with gall wasps.